Meta-analysis of the relationship between university students' anxiety and academic performance during the coronavirus disease 2019 pandemic - Tang, Yuxi; He, Weiguang (Frontiers in Psychology, 2023)
The current meta-analysis summarized the relationship between the anxiety and academic performance of university students during the 2019 coronavirus disease (COVID-19) pandemic. This study followed the PRISMA-P guidelines for meta-analysis. Four databases were searched (PsycINFO, Web of Science, PubMed, and Scopus) for papers published between December 2019 and June 2022. Finally, studies from five different countries were included in the analysis. A heterogeneity test was performed and a fixed-effects model used to calculate the main results. The results revealed a negative correlation between university students’ anxiety and academic performance (r = -0.211, k = 5, N = 1205). A subgroup analysis revealed that the regulatory effects were unclear regarding year of publication, country development level, student type, and anxiety type. Negative emotions engendered by the COVID-19 pandemic appear to be the most important factor through which university students’ anxiety leads to poor academic performance. During pandemics with severe global consequences, such as COVID-19, interventions against and prevention of university students’ negative emotions are important ways to improve university students’ mental health and academic achievement.